Bacteria and Mold Spore Heat Resistance in Guava Juice and Its Control by pH and Sodium Benzoate - Evelyn; Chairul (International Journal of Food Science)
Heat-resistant bacteria and molds can survive the pasteurization conditions used in high-acid fruit juices. The objective of this study was to evaluate the log reductions and thermal inactivation kinetics of spores of Bacillus subtilis bacteria and ascospores of Talaromyces flavus and Eupenicillium javanicum molds under influence of pH and sodium benzoate preservative. The spores were suspended in guava juice, processed at 90-100°C for B. subtilis and at 80-90°C for T. flavus and E. javanicum, and decimal reduction (D) values were estimated from the log survivor curves. Next, the effects of pH change (3.5-4.5) and 0.015% sodium benzoate addition on the D values of spores were investigated. Lower D values were obtained at higher temperatures (D100°C value of 2.32 min vs. D90°C value of 15.33 min for B. subtilis, D90°C value of 2.96 min vs. D80°C value of 59.52 min for T. flavus, and D90°C value of 1.58 min vs. D80°C value of 21.32 min for E. javanicum). The D values decreased further (to 1.8 min at 100°C for B. subtilis, to 2.33 min at 90°C for T. flavus, and to 1.49 min at 90°C for E. javanicum) when the pH of guava juice was decreased from 4.1 to 3.5. Inclusion of sodium benzoate in pH 3.5 juice enhanced the thermal inactivation of spores (D100°C value decreased to 1.4 min for B. subtilis, to 1.98 min for T. flavus, and to 1.34 min for E. javanicum). To conclude, the combination of low pH and sodium benzoate provided the best method for spore inactivation, which could enhance food safety and extend food’s shelf life.